Accessibility research in Malaysia - Hassan, Hasni; Jomhari, Nazean; Hishyam, Syariffanor (New York, United States, 2008)
In recent days, there is a tendency in Malaysia that more and more people are interested the research regarding the use of computing and information technology by the ageing population and people with disabilities. Below are some examples of these projects.